The Distribution Pattern of Mollusks Has Economic Value Concerning Substrate Characteristics in Lake Maninjau - Muhamad Suhaemi Syawal; Yusli Wardiatno; Sigid Hariyadi (Jurnal Biologi Tropis, 2020)
Lake Maninjau is one of the tectovulcanic type lakes in West Sumatra Province which is used as a food source in the presence of fauna groups such as mollusks. The main purpose of this study is to determine the distribution of mollusks concerning the substrate in Lake Maninjau. This research was conducted three times from March-September 2015 at seven points of the river estuary around Lake Maninjau. The result of the study shows that Corbicula moltkiana was mostly found at Pandan station, while Melanoides tuberculata and Anodonta woodiana were mostly found at Muko-Muko station. The distribution pattern of Corbicula moltkiana and Melanoides tuberculata shows a tendency to live in groups. The waters of the estuary around Lake Maninjau are dominated by sand with TN and TP concentrations ranged from 0.093 - 0.610 mg kg-1 and 0.427 - 2.137 mg kg-1, respectively.